Legal responsibility for negative effects of the vaccine: Nature and financial compensation - Alazzam, Farouq Ahmad Faleh; Al-zoubi, Tariq Muhammad Hussein; Aldghaim, Rafat A′yesh Issa; Al-Maagbeh, Mohmmed Mufadi; Bani-Meqdad, Mohammad Ali Mohammad; Shakhatreh, Hisham Jadallah Mansour (Edelweiss Applied Science and Technology, 2024)
The purpose of the article is to form an optimal scenario for receiving financial compensation for the negative consequences of vaccination. The object of the study is responsibility for unsuccessful vaccination. The scientific task is to form an approach to assessing possible scenarios for receiving adequate financial compensation. For this purpose, a methodology is presented that includes a scenario approach for applying the cognitive analysis method. As a result, the article presents a toolkit for studying the influence of factors of negative effects of vaccination through the definition of key legal and financial factors, their mutual influence, which was measured using correlation and regression analysis, and possible options and directions for choosing the optimal scenario for receiving financial compensation. The study has a limitation and does not take into account all possible factors, factors and negative effects. Prospects for further research should be aimed at a thorough analysis of the socio-demographic consequences of unsuccessful vaccination.